Маркетингова політика підприємства в умовах відновлення національної економіки (на прикладі ПрАТ Миргородський завод мінеральних вод) - Желізняк, Юлія Анатоліївна; Zhelezniak, Julia (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
В роботі проведено узагальнення ключових факторів відновлення національної економіки; систематизація підходів до напрямів відбудовування економіки України; обґрунтування ролі і властивостей маркетингової політики компаній у відновленні економіки; встановлення сучасних тенденцій попиту на ринку бутильованої питної води; виокремлення основних властивостей діяльності з управління попитом ПрАТ Миргородський завод мінеральних вод в сучасних умова; визначення напрямів удосконалення маркетингової політики ПрАТ Практичне значення кваліфікаційної роботи полягає в розробці пропозицій щодо вдосконалення маркетингової політики підприємств харчової промисловості в умовах відновлення національної економіки.

The key factors and imperatives of the recovery of Ukraine's national economy in the post-crisis period have been summarized. Theoretical approaches to the directions of economic rebuilding have been systematized, and the role of enterprises' marketing policy in this process has been determined. The current trends in the development of the mineral water market in Ukraine and the activities of PJSC "Myrhorod Mineral Water Plant" in demand management have been analyzed. Directions for improving the enterprise's marketing policy have been determined, in particular through the implementation of digital technologies, expansion of the product line, improvement of communication strategies, and development of the distribution network. The practical significance of the qualification work lies in the development of proposals for improving the marketing policy of food industry enterprises in the conditions of national economic recovery.
Marketing Policy of the Enterprise in the Conditions of National Economy Recovery (on the Example of PJSC Myrhorod Mineral Water Plant)
Науковий керівник: Коломієць Ганна Миколаївна, доктор економічних наук, професор кафедри економічної теорії та економічних методів управління
Keywords: SOCIAL SCIENCES::Business and economics::Economics; ПрАТ "Миргородський завод мінеральних вод"; маркетинговa політикa; попит; управління попитом; SWOT-аналіз; післявоєнне відновлення економіки України; PJSC "Mirgorod Mineral Water Plant"; marketing policy; demand; demand management; SWOT analysis; post-war recovery of the Ukrainian economy